Contraception as a risk factor for urinary tract infection in Port Harcourt, Nigeria: A case control study - Dienye, Paul O. (Afr J Prim Health Care Fam Med, 2011)
BACKGROUND: The concerted effort of government and donor agencies to limit fertility by the use of contraceptives has been reported in some studies to predispose to urinary tract infection (UTI). Similar studies have not been conducted in the General Outpatient Department (GOPD) of the University of Port Harcourt Teaching Hospital (UPTH). OBJECTIVES: This study was aimed at assessing the role of contraceptives in the development of UTI amongst adult females attending the GOPD of UPTH. METHOD: A case control study in which contraceptive users who attended the GOPD of the UPTH in four months, and an equal number of age-matched controls, were screened for UTI. The information obtained from them was entered into a specially designed pre-tested questionnaire for analysis. The results were analysed using SPSS version 14. RESULTS: A total of 150 contraceptive users and controls were evaluated. Their age range was 18–50 years, with a mean of 27.8 ± 5.3 years. Most of the participants belonged to the lower socioeconomic classes. The combined prevalence of UTI amongst the contraceptive users and the controls was 23.7%, with the contraceptive users at 35.3% and the controls at 12.0%. The association of UTI with contraceptive use was statistically significant, with McNemar's χ(2) = 16.28, p = 0.000, odds ratio (OR) = 2.9, 95% confidence interval (CI) = 1.7 – 5.3, attributable risk (AR) = 23.3, population attributable risk (PAR) = 11.7. The users of barrier contraceptives were more predisposed to UTI (OR = 17.30, 95% CI = 7.49 -39.96). CONCLUSION: Contraceptive use is a significant risk factor for acquiring urinary tract infection, with the barrier methods being more predisposing. Health education for the hygienic and safe use of family planning methods will prevent long-term complications.